PROBLEMS FACED WITH TRANSLATION OF TECHNICAL (RAILWAY) TERMS - Saydivaliyeva, Barno (Журнал иностранных языков и лингвистики, 2023)
Technical translations involve translation of texts dealing with electronics, medicine, law, economics, or sports. In words of one syllable, it means that technical translations deal with texts from the world of engineering, including chemistry, mathematics, information technologies, physics, economics, geography, etc. The number of technical fields is enormous, and terminology is expanding and changing daily.